In vitro activity of itraconazole against fluconazole-susceptible and -resistant Candida albicans isolates from oral cavities of patients infected with human immunodeficiency virus. - Barchiesi, F (1994)
A broth macrodilution technique, which was performed by following the recommendations provided by the National Committee for Clinical Laboratory Standards (document M27-P), was applied to study the in vitro activity of itraconazole against fluconazole-susceptible and -resistant Candida albicans isolates from the oral cavities of 100 patients infected with human immunodeficiency virus. The in vitro data demonstrated that itraconazole had good activity against the tested isolates; for 90% of all strains of C. albicans, MICs were 1 microgram/ml, and only one isolate was highly resistant to this triazole (MIC, > 16 micrograms/ml). However, the itraconazole MICs for the fluconazole-susceptible isolates were significantly lower than those for the fluconazole-resistant isolates; the MICs for 50 and 90% of the isolates tested were < or = 0.03 and 0.25 microgram/ml, respectively, for the fluconazole-susceptible isolates and 0.5 and 1 microgram/ml, respectively, for the fluconazole-resistant isolates (P = 0.00001). Our findings could be of clinical relevance because human immunodeficiency virus-infected patients who fail fluconazole therapy for oral and/or esophageal candidiasis may require itraconazole at doses higher than those used in standard therapy.